PREVALENCE OF POULTRY DISEASES AND THEIR INTERACTION WITH MYCOTOXICOSIS IN DISTRICT CHAKWAL: 1. EFFECTS OF AGE AND FLOCK SIZE - A. W. Yunus; M. K. Nasir; U. Farooq; J. Böhm (Journal of Animal and Plant Sciences, 2008)
Relationship of age and flock size with disease incidence in layer and broiler flocks, and interaction of diseases with mycotoxicosis was investigated. These investigations are based on postmortem examination of birds submitted to the Poultry Production Institute, Chakwal, during 2003-04. In broilers, incidence of coccidiosis, ascites, and infectious bursal disease (IBD) decreased with increase in flock size, while respiratory diseases seemed not to be affected by flock size. In layers, ascites and IBD followed the same trends as these were in broilers. However, incidence of coccidiosis in layers increased with increase in flock size. Effect of flock size on incidence of respiratory diseases was pronounced with negative correlation (-0.65). In broilers, coccidiosis was the most prevalent disease during 2nd and 3rd week of their life. After 4th week, ND and HPS were the most frequently encountered diseases. Incidence of respiratory diseases increased linearly with increase in age of the broilers (1.6, 12.8, 16.2, 25.7, and 43.7% in 1st, 2nd, 3rd, 4th, and 5th-8th weeks, respectively). Similarly, incidence of ND, and mycotoxicosis increased linearly with age. In layers, share of coccidiosis started increasing tremendously from 3rd week making it the most often encountered disease from 3rd week up to 3 month age. IBD and HPS were seen only during 1 to 2 and 2 to 3 month age, respectively. At 5 months of age 10.6 per cent ND outbreaks were observed whereas it was as18.1 per cent (maximum incidence) at 6 months of age. In various age groups, mycotoxicosis was found to have high correlation with ascites (r2, 0.7) in broilers, and ND (r2, 0.9) in both broilers and layers. The inverse relationship of management related diseases i.e., coccidiosis with flock size in broilers indicated lack of modern management practices on small farms. Similarly, the high positive correlation of mycotoxicosis with ND outbreaks is an indicative of one of the major contributing factors in vaccine failure in the study area. This necessitates more inputs from both feed millers and veterinarians in terms of farmer education and awareness on this issue.
Keywords: Prevalence; mortality; hemagglutination mycotoxicosis; coccidiosis